Multicarrier SPWM Control Techniques for Three Phase Eleven Level Diode Clamped Multilevel Inverter and Hybrid Inverter with Reduced Number of Components - N. Susheela; P. Satish Kumar (Institute of Advanced Engineering and Science, 2018)
A comparative analysis of three phase eleven level diode clamped multilevel inverter (DCMLI) and hybrid inverter is performed in this paper in which the later requires fewer carrier signals, less number of devices and gate drive circuits. The performance is evaluated using phase disposition (PD), alternate phase opposition disposition (APOD) and carrier overlapping (CO) sinusoidal pulse width modulation (SPWM) methods. The hybrid multilevel inverter has superior features over diode clamped multilevel inverters and is more efficient since the positive levels of the inverter that are generated by high frequency switches (level generation part), are reversed by low frequency switches (polarity generation part) when the voltage polarity is required to be changed for negative polarity. Therefore, the overall cost and complexity of the hybrid inverter are greatly reduced particularly for higher inverter output voltage levels. Simulation is performed for three phase eleven level diode clamped multilevel inverter and hybrid multilevel inverter using MATLAB/Simulink for induction motor load and the total harmonic distortion is evaluated at different load torques.